ASSESSMENT OF CARDIOVASCULAR HEALTH IN HYPERTENSIVE PATIENTS BASED ON TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Dr. Gautam Kumar; Dr. Chirag Malik; Dr. Mausumi Barthakur; Dr. Ashish Raj (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Cardiovascular complications among hypertensive patients represent a significant public health challenge, particularly in tertiary care settings. This study aimed to assess cardiovascular health status and identify associated risk factors among hypertensive patients in a tertiary care hospital.Methods: A hospital-based cross-sectional study was conducted among 400 hypertensive patients at a tertiary care center over six months. Participants were selected using systematic random sampling. Data was collected through structured questionnaires, clinical examinations, and laboratory investigations. Cardiovascular assessment included ECG, echocardiography, and carotid doppler studies where indicated. Statistical analysis was performed using SPSS version 25.0, employing descriptive statistics and appropriate inferential tests.Results: The study revealed that 58% of patients had uncontrolled hypertension, with physical inactivity (62.0%) and dyslipidemia (58.5%) being the predominant risk factors. Left ventricular hypertrophy was the most common complication (39.0%), followed by coronary artery disease (24.5%). Only 37.5% of patients showed good medication adherence. Uncontrolled hypertension was significantly associated with cardiovascular complications (54.8% vs 28.0%, p